Solve the equation: 13y − 5 = 9y + 27.

13y - 5 = 9y + 27 First we must collect all similar terms together on either side of the equation: 13y - 9y = 27 + 5. As you can see, if a term is moved to the other side of the equation, the opposite sign must be applied: 4y = 32. Now all the y's are collected together, we can follow the same approach as above in order get y on its own: y = 32/4 ...y = 8

Answered by Emma R. Maths tutor

9078 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

Solve the following simultaneous equations: 6j+4k=40; 7j-3k=-7


Expand the following: (4x+7)(7x-2)


How do I find the equation of a line connecting points a(p,q) and b(r,s)?


Solve the simultaneous equation: 2x + 3y = 6, 3x + 2y = 5.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences